Demand for complementary financial and technological tools for managing drought risk - Ward, Patrick S.; Spielman, David J.; Ortega, David L.; Kumar, Neha; Minocha, Sumedha (International Food Policy Research Institute, 2015)
Weather-related production risks remain one of the most serious constraints to agricultural production in much of the developing world. Financial and technological innovations that mitigate these risks have the potential to greatly benefit farmers in areas prone to such risks. In this study we examine farmers’ preferences for two distinct tools that allow them to manage drought risk: weather index insurance and a recently released drought-tolerant rice variety. We illustrate how these tools can independently address drought risk and demonstrate the potential for these tools to be combined in a complementary risk management product. Using a discrete choice experiment, we assess farmers’ preferences for these two tools independently and in a bundled package. Findings indicate that farmers are generally unwilling to pay for drought-tolerant rice independent of insurance, largely due to the yield penalty under normal conditions. When bundled with insurance, however, farmers’ valuation of the rice increases. Farmers value insurance on its own, but even more so when bundled with the drought-tolerant rice variety. The results provide evidence that farmers value the complementarities inherent in a well-calibrated bundle of risk management tools.